Strategic Guidelines for the Development of Small and Medium-sized Businesses: Evidence of Kazakhstan - Nurumov, A.; Saparova, B.; Alibekova, B.; Kuchukova, N.; Kairanbekov, B.; Mussina, A. (Montenegrin Journal of Economics, 2023)
The concept of strategic entrepreneurship predicts that the integration of op-portunity and profit-seeking behavior will lead to innovation. Countries that implement effective innovation policies and appropriate support measures demonstrate a high level of economic development, in which small and me-dium-sized businesses play an important role. Therefore, it is advisable to develop existing principles, methods and strategies for organizing innovation activities aimed at strengthening the market positions of enterprises, contrib-uting to meeting the requirements of the consumer market and ensuring mu-tually beneficial cooperation between business partners. The authors formu-lated conclusions and recommendations for improving the assessment of the effectiveness of the innovative development of small and medium-sized busi-nesses by summarizing foreign experience and, based on the trend model, extrapolated forecasting of the indicator "Enterprises with innovations" for 2022-2024. in order to determine the further development of the number of innovative and active enterprises of the Republic of Kazakhstan.
Keywords: Small and medium businesses; lending; entrepreneurship; financing; subsidies; strategic management